Icebergs rework shelf sediments to 500 m off Antarctica - Barnes, Peter W.; Lien, Reidar (Geology, 1988)
Icebergs and sea ice rework the sediments of high-latitude shelves, producing modern diamicts (ice-keel turbates) unrelated to glacial proximity. Off Antarctica, sidescan sonar data indicate the presence of ice-gouge features formed by the physical interaction between ice keels and the sea bed. These are recognized as incisions a few metres deep and tens of metres wide, in water depths up to 500 m. On the submarine bank tops and slopes off Wilkes Land and in the Weddell Sea, subcircular depressions 30 to 150 m in diameter, a washboard pattern, and hummocky bed features also represent iceberg-resting sites. The freshness of sea-bed morphology, nearby Holocene sediment ponding, and active hydraulic sedimentary processes indicate that the sea floor is being reworked by iceberg keels. Tabular iceberg drafts in excess of 330 m have been measured, and modeling studies suggest that nontabular iceberg drafts of 500 m are possible. We conclude that a modern ice-keel turbate deposit in the form of a poorly stratified diamicton is probably widespread on that part (54%) of the Antarctic shelf less than 500 m deep.
Keywords: Sørishavet; Weddellhavet; geofysikk; geologi; isberg; issfjell; oseanografi

Genetic population structure of Euphausia superba DANA in the Atlantic Sector of the Southern Ocean as demonstrated by different electrophoretic techniques - Fevolden, Svein Erik; Schneppenheim, Reinhard (Polar Biology, 1988)
Electrophoretic analyses of allele distributions at nine polymorphic gene loci were conducted in samples of Euphausia superba from the Bransfield Strait, off the South Orkney Islands, and from the south-eastern part of the Weddell Sea. The aim was to determine whether reported phenotypic differences between krill stocks from these areas could be linked to genotypic differences. Despite minor deviations of genotype distributions from Hardy-Weinberg expectations, the data gave no evidence of genetic heterogeneity over the sampled area, and the hypothesis of a single genetically homogeneous krill population could not be rejected. Genetic data for four selected loci were verified by using two different electrophoretic methods. Results from these two techniques yielded no discrepancies in interpretation of the data.
Keywords: Sør-Orknøyene; Sørishavet; Weddellhavet; genetikk; krill; marin biologi; plankton

Notes on Southern Ocean hydrography, sea-ice and bottom water formation - Foldvik, Arne; Gammelsrød, Tor (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
The Southern Ocean circulation and sea-ice distribution is briefly described. The formation of extremely cold bottom water in the Weddell Sea and its relation to the floating Ronne-Filchner Ice Shelves is discussed. It is shown that a concentrated swift eroding bottom current with anomalous low ratio transports the cold and dense ice Shelf Water from the shelf towards large depths. Comments are made on possible implications of this process for the large-scale deep-water circulation and for the interpretation of sediment cores.
Keywords: Sørishavet; Weddellhavet; geofysikk; havis; havstrømmer; hydrografi; isshelf; oseanografi

Geology, geophysics, and hydrocarbon potential of Antarctica continental margin of Weddell Sea - Hinz, K.; Kristoffersen, Yngve (AAPG Bulletin, 1987)
A prominent escarpment, called the Explora-Andenes Escarpment, has been recognized between long. 40°W, lat. 72°40^primeS and long. 10°W, lat. 69°20^primeS. It separates the continental margin from the Weddell Sea basin. Our recent MCS data have revealed the presence of some remarkably symmetric structures beneath a thick pile of tectonically undisturbed sediments. For example, two extensive wedge-shaped basement units occur between 20°W and 40°W. These units are characterized by a pattern of divergent reflectors which surround an elongated depression in basement. The northern wedge terminates against the Explora-Andenes Escarpment between 25°W and 30°W. The southern wedge, known as the Explora Wedge, shows a northward-dipping reflection pattern. The seismic characteristics suggest that both wedges consist of volcanic rocks. The basement depression is interpreted as a failed rift basin. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of "dipping reflectors." The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of dipping reflectors. The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures.
Keywords: Antarktis; Sørishavet; Weddellhavet; geofysikk; geologi

Genetic variation of Euphausia superba Dana in the Antarctic Peninsula waters - Fevolden, Svein Erik (Sarsia, 1986)
Nine samples of Antarctic krill collected at seven localities in the Palmer Archipelago and Bransfield Strait west of the Antarctic Peninsula were analysed for genetic variation at eight enzyme loci. Despite significant among sample heterogeneity in allele frequencies, no convincing evidence was found to support the hypothesis of distinct genetic stocks of Euphausia superba in the investigated area. Allele frequency distributions could not be correlated to regional differences in size patterns. Allelic proportions at the PGI locus did not indicate that the investigated krill was genetically different from E. superba from the Weddell Sea region (from earlier investigations). Deviations of genotypes, or allele frequencies from those expected under Hardy-Weinberg equilibrium, however, may indicate regional, or yearly variation due to occasional selection.
Keywords: Sørishavet; Weddellhavet; genetikk; krill; plankton

Geophysical evidence for the East Antarctic plate boundary in the Weddell Sea - Kristoffersen, Yngve; Haugland, Kristen (Nature, 1986)
An improved Gondwanaland reconstruction compatible with geological and geophysical information from the surrounding oceans and continents seems to require microplates to solve the enigmatic pre-early-Mesozoic tectonic relation between West and East Antarctica1. New multi-channel seismic reflection data from the southeastern Weddell Sea acquired during the 1984–85 Norwegian Antarctic Research Expedition (NARE) have outlined a linear WSW–ENE-trending basement ridge buried below the continental slope over a distance of 700 km. This structural high truncates the trend of the large sedimentary basins below the Filchner and Ronne ice shelves and may continue to within a few hundred kilometres of the Antarctic Penninsula. We interpret the basement ridge as part of the East Antarctic plate boundary during the break-up of Gondwana. The morphology and structure of this boundary show greater apparent similarity to a rifted or obliquely rifted margin than to the sheared margin which is predicted by current reconstructions2,3. A linear East Antarctic plate margin extending to the vicinity of the Antarctic Peninsula makes any post-rift micro-plate motion in the Weddell Embayment unlikely.
Keywords: Antarktis; NARE 1984/85; Weddellhavet; geofysikk; geologi; tektonikk

Hydrographic observations on the southern Weddell Sea shelf break - Foldvik, Arne; Gammelsrød, Tor (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; hydrografi; oseanografi

Oceanographic conditions on the Weddell Sea Shelf during the German Antarctic Expedition 1979/80 - Foldvik, Arne; Gammelsrød, Tor; Slotsvik, Noralf; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; hydrografi; isshelf; oseanografi

Circulation and Water Masses on the Southern Weddell Sea Shelf - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Hydrographic observations from the Weddell Sea during the Norwegian Antarctic Research Expedition 1976/77 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; hydrografi; kontinentalsokkel; observasjoner

Physical oceanography studies in the Weddell Sea during the Norwegian Antarctic Research Expedition 1978/79 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; havstrømmer; hydrografi; isshelf; oseanografi

Bottom Currents Near the Continental Shelf Break in the Weddell Sea - Foldvik, Arne; Kvinge, Thor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; kontinentalsokkel; kontinentalsokler; tidevannsstrømmer

Geophysical studies in the southern Weddell Sea - Haugland, Kristen; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; geofysikk

Seismic investigations in the Weddell Sea Embayment - Haugland, Kristen; Kristoffersen, Yngve; Velde, Anders (Tectonophysics, 1985)
Keywords: Antarktis; NARE 1976/77; NARE 1978/79; Weddellhavet; ekspedisjoner; seismologi

Iceberg research and other glaciological studies from K/V "Andenes" - Kristensen, Monica; Orheim, Olav (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; glasiologi; isfjell

Impact of Grounded Icebergs on the Hydrographic Conditions Near the Filchner Ice Shelf - Nøst, Ole Anders; Østerhus, Svein (Ocean, Ice, and Atmosphere: Interactions at the Antarctic Continental Margin, 1985)
Keywords: Sørishavet; Weddellhavet; havis; hydrografi; isberg; isfjell; isshelf; sjøis; vannmasser

Marine geological studies on the Weddel Sea shelf - Solheim, Anders; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; marin geologi

Size Frequency Pattern of Euphausia Superba in the Antarctic Peninsula Waters in the Austral Summer of 1983 - Fevolden, Svein Erik; George, Robert Y. (Journal of Crustacean Biology, 1984)
In the austral summer of 1983, schools of krill from Bransfield Strait and Palmer Archipelago were analyzed for composition in terms of size frequencies and maturity stages. Juveniles dominated in all schools, and mature animals never exceeded 6.8% of the animals at any sampling site. Gravid females were encountered in only four out of 15 schools and were never more frequent than 1.8% of the animals in any school. Among subadults and juveniles the largest animals were found on the inside of Palmer Archipelago. Smaller nonreproductive animals were on the outside and in Bransfield Strait. A second group of juveniles, in a size range of 12-15 mm, was more pronounced north of Crocker Passage than south of the Passage. Their potential origin from a more slowly growing and later spawning Southern Weddell Sea population is discussed. Lack of reproductive animals in the Bransfield/South Shetlands vicinity may reflect yearly variation in this region. A hypothesis is put forward on the basis of this study that Palmer Archipelago is a nursery ground for krill spawned elsewhere. The sites of origin of this krill could be ascertained on the basis of studies of enzyme polymorphism in these populations.
Keywords: Sørishavet; Weddellhavet; krepsdyr; krill; marin biologi; plankton

Biokjemiske studier over antarktisk krill - Ellingsen, Trond E; Norges tekniske høgskole Institutt for teknisk, biokjemi (Institutt for teknisk biokjemi, 1982)
Keywords: Bouvetøya; Sørishavet; Weddellhavet; biokjemi; krill; lipider; lyskreps; marinbiologi

Evidence for a late Wisconsin glaciation of the Weddell Sea - Elverhøi, Anders (Nature, 1981)
Keywords: Sørishavet; Weddellhavet; forskning; glasiologi; sedimentologi; stratigrafi

Hydrographic and current measurements in the southern Weddell Sea 1979/80 - Gammelsrød, Tor; Slotsvik, Noralf (Polarforschung, 1981)
During the 1979-1980 expediton with the icebreaker Polarsirkel we had an excellent opportunity to study the physical oceanography of the inner part of the Weddell Sea. The ship followed the ice shelf barrier from Cape Norwegia at about 15 °W, and due to favourable ice conditions, it was able to penetrate all the way to the Antarctic Peninsula (60 0W). In this preliminary report we give a review of the physical oceanography programme which mostly consists of hydrographic (CTD) stations near the barrier, and also sorne current and water level measurernents. The different water masses observed are described and the possibility for a tidal-drlvcn upwelling near the ice shelf barrier is indicated.
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; havis; hydrografi; isshelf; oseanografi; sjøis; sjøvann; vannmasser

Morphology of the Weddell Sea and southwest Indian Ocean - Johnson, G Leonard; Vanney, Jean-René; Elverhøi, Anders; LaBrecque, John L (Deutsche Hydrografische Zeitschrift, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; tektonikk

Krill off Bouvetøya and in the southern Weddell Sea with a description of larval stages of Euphausia crystallorophias - Fevolden, Svein Erik (Sarsia, 1980)
In the austral summer 1978/79 samples of krill were taken off Bouvetøya and in the southern Weddell Sea. Off Bouvetøya Euphausia superba Dana was the dominant species, but the population pattern indicates that the individuals found there were expatriates from other areas. For the first time larvae of E. superba were found in significant amounts in the southern Weddell Sea. Except from shallow water and the most southern position, they were equal in abundance to the larvae of E. crystallorophias Holt & Tattersall. Larval stages of the latter are described as is the successive spawning that takes place among the three species of krill found in the southern Weddell Sea.
Keywords: Bouvetøya; NARE 1978/79; Weddellhavet; dyreplankton; krill; plankton; zooplankton

Flow Around Icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; observasjoner; oseanografi; sjøvann